2009
DOI: 10.1371/journal.pone.0006377
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation-Induced Oxidative Stress Alters miRNA Expression

Abstract: BackgroundMicroRNAs (miRNAs) are small, highly conserved, non-coding RNA that alter protein expression and regulate multiple intracellular processes, including those involved in the response to cellular stress. Alterations in miRNA expression may occur following exposure to several stress-inducing anticancer agents including ionizing radiation, etoposide, and hydrogen peroxide (H2O2).Methodology/Principal FindingsNormal human fibroblasts were exposed to radiation, H2O2, or etoposide at doses determined by clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
241
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(257 citation statements)
references
References 22 publications
13
241
0
3
Order By: Relevance
“…The change of miRNAs expression in response to oxidative stress has been investigated in different cells and tissue samples such as human fibroblasts and vascular and adipose tissues [48,23]. However, the effect of TBHP-induced oxidative stress on miRNA expression has not been investigated in mouse testis so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of miRNAs expression in response to oxidative stress has been investigated in different cells and tissue samples such as human fibroblasts and vascular and adipose tissues [48,23]. However, the effect of TBHP-induced oxidative stress on miRNA expression has not been investigated in mouse testis so far.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in miRNAs expression may occur following exposure to stress-generating agents. Simone's in vitro study on human fibroblast indicated that miRNAs may play a role in cellular defense against oxidative stress [48]. Nonetheless, there are limited studies to demonstrate the role and function of miRNAs in testis tissue and their relationship with male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies demonstrated that the expression changes for certain miRNAs could be attributed to increased ROS production [45][46][47][48]. To elucidate the mechanism responsible for miR-214 down regulation in erythroid cells in response to stress, we investigated the relationship between miR-214 expression and ROS production.…”
Section: Ros-dependent Downregulation Of Mir-214 In Erythroid Cellsmentioning
confidence: 99%
“…EZH2 is the catalytic core component of PRC2 complex which conducts tri-methylation reaction at lysine 27 (K27) of histone 3 (H3), resulting in increased level of H3K27me3 [61,62]. Fine-tuned regulation of EZH2 is closely implicated in cell proliferation, differentiation, senescence and apoptosis under normal settings; however, deregulated EZH2 is associated with a number of disorders including various cancers [48,54]. To this end, we here tested the hypothesis that EZH2 could be a downstream target of Nrf2-miR-214 in erythroid cells against exotic stress.…”
Section: Ezh2 Is a Downstream Target Of Nrf2-mir-214 Against Oxidativmentioning
confidence: 99%
“…when increasing let-7a or let-7b levels) or radio-resistance (i.e. when reducing let-7 g levels) in RAS mutant pancreatic and lung cancer cell lines [22][23][24]. We acknowledge that our results are hypothesis-generating.…”
Section: Discussionmentioning
confidence: 76%